AI-Integrated Problem-Based Learning Model for Digital Economic Literacy: A Systematic Literature Review - Sri Mulyati; Toni Wijaya; Iskandar Iskandar; Yeyen Suryani; Rani Tania Pratiwi; Shelia Maharani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
Abstract The rapid integration of AI into higher education offers transformative opportunities for active learning pedagogies, particularly Problem-Based Learning, while elevating Digital Economic Literacy. However, the intersection of AI-integrated PBL and DEL remains systematically underexplored. This study presents a Systematic Literature Review to identify, evaluate, and synthesize evidence regarding the implementation and impact of AI-integrated PBL on DEL. Following PRISMA guidelines and the PICo framework, a search was conducted across Scopus, Google Scholar, ERIC, and IEEE Xplore databases. From an initial pool of 173 articles, 35 high-quality, peer-reviewed studies published between 2020 and 2026 were selected for thematic synthesis. The findings reveal five key themes: (1) pedagogical frameworks for AI-PBL integration, (2) AI tools and technologies within the PBL context, (3) impacts on DEL competencies, (4) student engagement and learning outcomes, and (5) challenges and enabling factors for implementation. The review demonstrates that AI-integrated PBL enhances students' critical thinking, digital problem-solving, economic reasoning, and technological adaptability when supported by appropriate pedagogical scaffolding, institutional support, and clear ethical guidance.